Pengaruh Kualitas Audit Dan Opini Audit Going Concern Terhadap Manajemen LabaStudi Empiris pada Perusahaan Perbankan di Indonesia yang Terdaftar di Bursa Efek Indonesia pada Tahun 2011-2013 - Hendarwati, Pratiwi, Fauzan,SE,M.Si (2016)
Earnings Management is unavoidable and can be role of the auditors/ KAP as a gatekeeper capitak markets that can provide assurance on the quality of financial reporting of public cimpanies. The approved from the reset is to test influence from KAP big four, KAP Indrustries Specialisation, and willingness to report and accurated of the going concern audit opinion to earnings management from the banking companies registered on Bursa Effect Indonesia. The population in this reset is all of banking companies registered on Bursa Effect Indonesia during perioded 2011-2013. The methods sample taking using purposive sampling according to the criteria that have been determined. amount of samples that collected is 81 companies. Becouse of outliers data 6 companies, then sample to be 75 companies. Before testing the hypothesis done first classical assumtion test: normalitas test, multikolinearitas rest, autokorelation test and heteroskedastisitas test. Hypothesis testing in this reset using multiple regretion with significant model test (uji F), koefisien determination, and than parcial regretion (Uji t). Result from this reset showing determination coefition is getting value 0.116 that means 11.6% audit quality and going concern audit opinion and residual of the reset 88.4% appected by variables outside the model. Overall KAP Spesialis Industries no effect to earnings management, while KAP Big Four and willingness to report and accurated of the going concern audit opinion effect to earnings management.